From Inclusion to Social Exclusion in Resource Stewardship among Members of Migrant Bilik Families in Pantu, Sri Aman - Dimbab, Ngidang (Springer Singapore, 2017)
It is evident that migration and labour mobility have had a major impact on the lives of Iban longhouse dwellers. One result is the problem of social exclusion and vulnerability which is manifested in a number of ways, not least the loss of control over livelihoods and customary rights. These issues are considered here in five major sections. The first part offers a brief overview of the research setting, the three longhouse communities of Empaling, Tekoyong and Munggu Ubah in the subdistrict of Pantu, Sri Aman that have experienced rural–urban migration. The second part of the analysis deals with social inclusion associated with the role of an inheritance institution in resource stewardship. The third part examines the evolution of a resource stewardship by default as an informal arrangement linking to the social position of community leadership as the custodian of adat or customary law. The fourth section explains how resource stewardship by default interacts with economic opportunity provided for by a joint venture oil palm project. The fifth addresses the concept of social exclusion and resource conflict associated with the collusion of vested interests from within and without the communities against the interests of absentee landowners, illustrated by a pair of case studies. The discussion suggests that the integrity of community leadership as a custodian of traditional adat law and land rights is compromised.